Synthesis of magnetite using petai (Parkia speciosa) peel extract with ultrasonic waves as reusable catalysts for biodiesel production from waste frying oil - Maya Rahmayanti; Annisa Nurul Syakina; Triastuti Sulistyaningsih; Budi Hastuti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Magnetite synthesis using petai (Parkia speciosa) peel extract using the sonochemical method (Fe3O4-PPE) has been successfully carried out. Fe3O4-PPE is applied as a catalyst in biodiesel production. This study aimed to determine the physical and chemical characteristics of Fe3O4-PPE and its ability as a reusable catalyst in biodiesel production using waste frying oil as the primary raw material. Characterization of Fe3O4-PPE was carried out using FTIR, XRD, and PSA instruments. Biodiesel was produced in 3 reaction cycles with the same Fe3O4-PPE catalyst. The results of the FTIR characterization showed that the Fe3O4-PPE catalyst had Fe-O bonds from Fe3O4 and -OH phenolic groups, -C-O, -C=C aromatic compounds derived from petai peel extract. The crystal size of the Fe3O4-PPE catalyst based on the results of calculations using Debye-Scherrer from the XRD chromatogram is 9.41 nm. The particle size of the Fe3O4-PPE catalyst based on analysis using PSA was divided into three groups, namely, 5.4 nm, 195 nm, and 2702.6 nm. Fe3O4-PPE was successfully used as a reusable catalyst for three cycles of biodiesel production using waste frying oil as raw material. The characteristics of Fe3O4-PPE before and after being used as a catalyst did not change. Based on GC-MS analysis, the fatty acid methyl ester (FAME) composition of biodiesel is palmitic acid and oleic acid.